Four new species of the microcaddisfly genus Alisotrichia Flint (Trichoptera: Hydroptilidae) from southeastern Brazil - Santos, Allan Paulo Moreira (Zootaxa, 2011)
Alisotrichia Flint, 1964 is an exclusively New World genus of microcaddisflies (Hydroptilidae), currently assigned to Leucotrichiini. Until now, this genus contained 51 species, of which only 1 has been described from Brazil. In this paper, 4 new species are described from Southern Brazil, 3 in the A. orophila Group (A. holzenthali sp. nov., A. macae sp. nov., and A. nessimiani sp. nov.) and one in the A. hirudopsis Group (A. ubatuba sp. nov.). The new species are separated by features of the terminal abdominal segments and structures of the male genitalia.